Maia's birthday party - Fernandez, Yvette; Lim, Nicole Anne (Quezon City Adarna House, Inc., 2012)
Maia is five years old today. She's having spaghetti, cake, and ice cream at the orphanage where she used to live. It's a happy day for Maia and her friends. Come and join her birthday!.
"A book in 2 languages." -- Cover.
This book is recommended for children ages 8 and above.
Text in English and Filipino.
Keywords: Birthdays -- Juvenile fiction; Children's stories, Philippine (English); Children's stories, Filipino